Procedure For Managing Export And Import Documents By PT. Adhigana Pratama Mulya Belawan - Angelita Rohana Sibagariang; Syarifur Ridho; Dirhamsyah Dirhamsyah; Fadiyah Hani Sabila (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
This paper aims to find out the process of managing export and import documents by PT Adhigana Pratama Mulya Belawan branch, the process starts from before the arrival of the ship to the port of Belawan, the agent has prepared the documents needed by the ship in loading and unloading activities. The data collection method used by the author in writing this paper is the field observation method (field research) and the library method (library research) to find out more closely how the company PT. Adhigana Pratama Mulya Belawan branch in carrying out export and import document management activities. The problems faced in the process of managing export and import documents are frequent quantity differences that cause revisions to documents. Good cooperation and coordination between shipping companies and related agencies in the management of export and import documents is needed for the smooth service of handling export and import documents